Emerging Vector borne zoonoses: eco-epidemiology and public health implications in India - Ramesh C Dhiman (Frontiers Media S.A., 2014)
The diseases originating from animals or associated with man and animals are remerging and have resulted in considerable morbidity and mortality. The present review highlights the re-emergence of emerging mainly zoonotic diseases like chikungunya, scrub typhus, extension of spatial distribution of cutaneous leishmaniasis from Western Rajasthan to Himachal Pradesh, Kerala, and Haryana states; West Nile virus to Assam, and non- endemic areas of JE like Maharashtra and JE to Delhi; Crimean Congo Hemorrhagic Fever making inroads in Ahmedabad; reporting fifth parasite of human malaria with possibility of zoonosis have been highlighted which necessitates further studies for prevention and control. Emphasis has been given on understanding the ecology of reservoir hosts of pathogen, micro niche of vector species, climatic, socioeconomic risk factors etc. Development of facilities for diagnosis of virus from insects, reservoirs and human beings (like BSL4 which has been established in NIV, Pune), awareness about symptoms of new emerging viral and other zoonotic diseases, differential diagnosis, risk factors (Climatic, ecological and socioeconomic) and mapping of disease specific vulnerable areas, mathematical modeling for projecting epidemiological scenario, are needed for preparedness of public health institutes. It is high time to understand the ecological link of zoonotic or anthroponotic diseases for updated risk maps and epidemiological knowledge for effective preventive and control measures. The public health stakeholders in India as well as in south East Asia should emphasize on understanding the eco-epidemiology of the discussed zoonotic diseases for taking preventive actions.